Neonatal Murine Model of Coxsackievirus A2 Infection for the Evaluation of Antiviral Therapeutics and Vaccination - Ji, Wangquan; Qin, Luwei; Tao, Ling; Zhu, Peiyu; Liang, Ruonan; Zhou, Guangyuan; Chen, Shuaiyin; Zhang, Weiguo; Yang, Haiyan; Duan, Guangcai; Jin, Yuefei (Frontiers in Microbiology, 2021)
Coxsackievirus (CV) A2 has emerged as an important etiological agent in the pathogen spectrum of hand, foot, and mouth disease (HFMD). CVA2 infections are generally mild, but some infections rapidly worsen, posing a serious threat for children’s health. However, compared with enteroviruses 71 frequently detected in fatal cases, limited attention has been paid to CVA2 infections because of its benign clinical course. In the present study, we identified three CVA2 strains from HFMD infections. The cell-adapted CVA2 strain HN202009 was employed to intramuscularly inoculate five-day-old BALB/c mice, which developed remarkably neurological signs such as ataxia, hind-limb paralysis, and death. Histopathological determination showed neuronal degeneration and gliosis in the central nervous system, severe damage in skeletal muscle, viral myocarditis and pulmonary hemorrhage. We detected viral replication in multiple organs and tissues from infected mice, and CVA2 exhibited strong tropism to muscle tissue. The severity of illness was associated with abnormally high expression of inflammatory cytokines, including interleukin (IL)-6, IL-10, tumor necrosis factor α, and monocyte chemotactic protein 1. However, the blockade of these proinflammatory cytokines had no obvious protection. In addition, an experimental formaldehyde-inactivated CVA2 whole-virus vaccine induced immune response in adult mice and the original CVA2 antiserum were effective against CVA2. Furthermore, the inactivated CVA2 whole-virus vaccine could successfully generate immune protection in neonatal mice. These results suggest the successful development of a neonatal mouse model of CVA2 infection, providing a useful tool for the study of CVA2 infection.